Left ventricular response to dynamic exercise in young cyclists - Rowland, T.; Unnithan, V.; Fernhall, B.; Baynard, T.; Lange, C. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The purpose of this study was to compare cardiac physiological and dimensional responses to exercise in highly trained young male cyclists (mean age 13.7 +/- 1.0 yr) with those of nontrained boys. METHODS: Ventricular systolic and diastolic dimensions were measured by two-dimensional echocardiography, and stroke volume was estimated by Doppler echocardiography during a progressive maximal upright cycle test. RESULTS: At rest, the cyclists demonstrated larger left ventricular dimensions relative to body size than the nonathletes. Maximal stroke index and cardiac index were significantly greater in the cyclists. The pattern of stroke volume response to exercise was similar in the two groups, with an early rise and then plateau to exhaustion. Left ventricular diastolic dimension increased slightly at onset of exercise and then gradually declined as workload increased in both groups. CONCLUSION: Factors responsible for the greater maximal stroke volume in young endurance athletes involve those variables that contribute to resting left ventricular diastolic filling (preload).